The Impact of Money Supply on National Income: An Empirical Analysis of Bangladesh - Shamim Uddin (Generasi Sains Indonesia, 2024)
This study explores the complex issue of relationship between money supply and national income in Bangladesh. It narrates the determinants of per capita GDP based on data on seventeen years of information on 2006-2022. It uses a multiple regression model to assess different macroeconomic variables, such as the inflation rate, GDP growth, the real interest rate (RIR), and the narrow (M1), broad (M2), and total (M3) money aggregates and, therefore, provides a holistic examination of the factors that affect the per capita GDP. The model scores highly in explanatory power, as its R-squared estimate suggests that the chosen variables have an explanatory power that is capable of attributing a significant part of the range of variation of per capita GDP. More importantly, real interest rates have a statistically significant negative correlation with per capita GDP, such that an increase in the real interest rates is associated with a decrease in national income. On the contrary, the correlation between the per capita GDP and the different money supply indicators (M1, M2 and M3) have minimal statistical significance and this indicates that other determinants have a stronger impact on national income in the Bangladeshi environment. The findings provide policymakers and economists with practical information that is relevant to the management of economic growth and the monetary policy in Bangladesh.